Traumatic Reflection In Dian Purnomo's: Perempuan Yang Menangis Kepada Bulan Hitam - Qadriani, Nurlailatul; Sakaria, Sakaria (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. In contemporary Indonesian literature, trauma analysis typically employs psychoanalytic or cognitive psychology. The application of Skinner's behaviorism theory to understand the mechanism of trauma in main characters in literature is still quite controversial. However, it can offer different perspectives on how the main character can develop a strategy for coping with trauma. This study analyzes the traumatizing references made by the main character, Magi Diela Tolo, in Perempuan Yang Menangis Kepada Bulan Hitam by Dian Purnomo. The three main areas of focus for the study are factors that cause trauma, forms of trauma that arise, and the methods used by the main character to recover from the experienced trauma. This research employs a descriptive qualitative method with an isi analysis technique. Data collection is conducted by examining the text and analyzing it using the concepts of reinforcement and stimulus-response from behaviorism theory, B.F. Skinner, and then analyzing the results based on the study's findings. According to the study's findings, the three main factors that contribute to Magi trauma are beliefs in Yappa Mawine customs, peer pressure, and persistent discrimination from the general public. This trauma manifests as psychological symptoms like depression and anxiety, as well as physical symptoms like physical ailments. Magi outlines three strategies for coping with this trauma: treating the person as an internal source of strength, reflecting on oneself using positive thinking, and working to improve the environment to aid in the healing process. This study contributes to the field of literary psychology by offering behaviorism as an alternative to trauma analysis in Indonesian novels. It is hoped that all of the information regarding this strengthening mechanism will give rise to fresh ideas about behavioral therapy for trauma, particularly regarding gender-based and traditional victim violence. In addition, this study adds to our understanding of how women's characters in Indonesian culture illustrate resilience in the face of societal traumaKeywords: Trauma, Behaviorism, Reinforcement, Women, Dian Purnomo's Novel